Considering and Reviewing Economics for Everyone - Fatemeh Mehraban (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper reviews the concepts mentioned in the book "Economics for Everyone", and provides a critical view on the content of the book. The emphasis of the book and the author's reasons for writing the book is that there is not enough exchange of information between economic students and populace about economic issues. Although the book  presents difficult and complex economic concepts in macroeconomics for public community through  simple,, eloquent, and fluent language,  the book ., the book does not seem suitable for those people people who lack the knowledge of economy because they need to know the assumptions and concepts in this field. Furthermore, overemphasis on the simplification of the concepts has led the author to neglect many of the prerequisite concepts. This leads to the reduced cohesion andlogical arrangement in details.Despite the overall coherence and the presentation of the analysis based on the neo-classical view, it seems that the review and reorganization of work in such a way that the reader can understand the relationship between the concepts listed and the course bookhelps to increase the coherence of the book.